2020
DOI: 10.1159/000506666
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hearing Aid Benefit Using Patient-Reported Outcomes and Audiologic Measures

Abstract: Purpose: To determine the contributions to hearing aid benefit of patient-reported outcomes and audiologic measures. Methods: Independent review was conducted on audiologic and patient-reported outcomes of hearing aid benefit collected in the course of a middle ear implant FDA clinical trial. Unaided and aided data were extracted from the preoperative profiles of 95 experienced hearing aid users, and the relationships between a patient-reported outcome and audiologic measures were assessed. The following data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Explanations based on audiometric findings, however, are quite likely to fall short in the self-assessment of hearing abilities. As in established questionnaires, such as the Speech, Spatial, and Qualities of Hearing Scale ( Gatehouse & Noble, 2004 ) and the APHAB ( Cox & Alexander, 1995 ), EMA still captures the subjective perspective on activity limitations, and perfect agreement with audiometric findings is neither intended nor achieved ( Banh et al., 2012 ; Dornhoffer et al., 2020 ; von Gablenz et al., 2018 ). Complex, temporally dynamic interactions of personality and context, which probably impact the self-assessment of abilities, are in general difficult to disentangle and certainly require complementary methods and a larger study sample when EMA data are concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Explanations based on audiometric findings, however, are quite likely to fall short in the self-assessment of hearing abilities. As in established questionnaires, such as the Speech, Spatial, and Qualities of Hearing Scale ( Gatehouse & Noble, 2004 ) and the APHAB ( Cox & Alexander, 1995 ), EMA still captures the subjective perspective on activity limitations, and perfect agreement with audiometric findings is neither intended nor achieved ( Banh et al., 2012 ; Dornhoffer et al., 2020 ; von Gablenz et al., 2018 ). Complex, temporally dynamic interactions of personality and context, which probably impact the self-assessment of abilities, are in general difficult to disentangle and certainly require complementary methods and a larger study sample when EMA data are concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were revealed in another study evaluating subjective satisfaction following VSB surgery [ 13 ]. In a study on the assessment of the benefits of conventional HAs, significant increases in the AV subscale scores were observed in the aided condition relative to that in the unaided condition [ 14 ]. We assumed that as the hearing threshold decreased after surgery, the amount of external sound perceived increased, and this noise made some patients feel uncomfortable.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies regarded patient-reported outcome measures (PROMs) as indicators of benefits [Wilson and Stephens, 2003;Williams et al, 2009;Hickson et al, 2010;Hickson et al, 2014;Chang et al, 2016;Wu et al, 2019]. Other studies assessed benefits using both objective and subjective measures [Mendel, 2007;Chang et al, 2008;Meister et al, 2015;Dornhoffer et al, 2020;Kwak et al, 2020]. There is some ambiguity in the relationships between objective audiologic tests and PROMs, and research results are far from consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Meister et al [2015] found that the pure tone aver-age (PTA) thresholds were negatively associated with subjective outcomes [Meister et al, 2015]. However, other studies reported absent or low-to-weak correlations among PROMs and hearing sensitivity and speech recognition scores [Mendel, 2007;Dornhoffer et al, 2020;Kwak et al, 2020]. Studies in this area often have a limited range of HL -concentrated in moderate [Mendel, 2007;Wu et al, 2019;Dornhoffer et al, 2020;Kwak et al, 2020].…”
Section: Introductionmentioning
confidence: 99%